Theoretical Approaches to the Study of the Economy of Religion - Zoya Shwed; 10.29202/fhi/11/9 (International Society of Philosophy and Cosmology, 2019)
The purpose of the paper is to identify and analyze the basic principles of the economy of religion. Consideration of the methodological features of the study of economics and religion should ensure the definition of the conditions for the application of an interdisciplinary approach, in the relationship between the economy and religion. This involves solving the following tasks: first, to reveal the content of the modern approaches, to understanding the relationship between religion and the economy, as a special area of public life, and secondly, to analyze the main features of the influence of religion on the economy, and the influence of the economy on religion. The theoretical basis of the study is based on several groups of sources, which highlight the problem of the relationship between religion and the economy. First, it is the legal documents in which the object of the legal regulation is religion and its institutional foundations. Secondly, these are theoretical works that cover the issues of the interdependence of economic and religious spheres. Thirdly, there are religious studies, which argue for the need to establish the discipline of religious studies, and separate from it the economy of religion as an independent branch of knowledge. Originality: The author proves that in analyzing the relationship between religion (as an institution) and economics, it is necessary to take into account their common social nature. This circumstance leads to the conclusion that the activities of religious organizations are observed and controlled by the humanitarian policy of the State. In order to ensure the rights and freedoms of its citizens, the State resorts to legislative activity, which determines the content and features of 'State vs Religion' relations, including also the economic sphere. The results of this legislative activity are expressed in the relevant regulatory acts and laws. Conclusions: The relationship between the economy and religion is found in the praxiological and institutional levels. The religious traditions of the world, in their doctrines, contain elements of Canon Law that regulate economic activity in the private and public areas. These elements determine the content and features of economic practices and form a special perception of the nature and function of the economy. The attention of the State to these factors, contribute to the expansion of the rights and freedoms of its citizens, which affects the results of sustainable economic development.